Assessment of training needs of poultry farmers in Zaria local government area of Kaduna State, Nigeria - Issa, F. O.; Kagbu, J. H.; Mani, J. R.; Maccido, M. A. (ADAN JOURNAL OF AGRICULTURE, 2024)
This study assessed the training needs of poultry farmers in Zaria Local Government Area of Kaduna State, Nigeria. The study specifically described the socio-economic characteristics of poultry farmers, identified the training needs by poultry farmers, identified the institutional support enjoyed by poultry farmers, and identified farmers’ constraints to poultry production. One-hundred and fifty (150) poultry farmers were used as sample for this study. Interview schedule was used to collect relevant data. Descriptive statistics was used to analyze the data collected. Result obtained shows that farmer have high level of education. Also, proper record keeping was the major training need by poultry farmers while new agricultural technology ranked as the major institutional support enjoyed by the farmers. High cost of input was the major constraints to poultry production in the study area. This paper concluded that poultry farmers need training on adequate record keeping. It recommended agricultural institutions such as government, private organizations and NGOs should support farmers through intensive training and re-training especially on identified areas of needs in order to increase their productivity.